Anterior intra-pelvic approach and corona mortis vascular anastomoses: A clinical anatomical study shows high frequency - Güzel Yunus; Elmadağ Nuh Mehmet; Arazi Mehmet; Özen Kemal Emre; Çiçekcibaşı Aynur Emine (Vojnosanitetski Pregled)
Background/Aim. Corona mortis vascular anastomoses (CMVA) must be located during surgical gold standard treatment method for displaced acetabular fractures. This study aimed to answer the following questions: What is the clinical frequency observed of CMVA? What is the composition of CMVA: arterial, venous or a combination? Methods. A retrospective review was made of 31 patients (24 males, 7 females; mean age 43.5 years) who underwent surgery for acetabular fractures between 2011 and 2015. The anterior intra-pelvic (AIP) approach was applied to all patients. By examination of the intraoperative CMVA compositions, the frequency of CMVA was determined together with identification of venous or arterial formation and distance from the pubic symphysis. Results. CMVA was observed during dissection in 29 (94%) patients and was ligated. In 14 (45%) patients, CMVA was recorded as venous, in 7 (23%) patients as arterial and in 8 (26%) patients as both. The mean distance of CMVA from the pubic symphysis was 35.9 mm (range 21.6–48.7 mm). Conclusion. The results showed very high CMVA frequency in the AIP approach, higher than previously reported in the English literature. Orthopedic surgeons should be aware about CMVA while doing this approach in surgical treatment of acetabular fractures.